Overweight of Slovenian school children: Prekomerna prehranjenost slovenskih osnovnošolskih otrok - Marčun Varda, Nataša; Hanželj, Natalija (Acta Medico-Biotechnica, 2021)
Purpose: The purpose of our research was to determine the prevalence of overweight and obese school children 6-15 years of age. We wanted to determine the children´s knowledge about obesity and treatment for obesity. We also wanted to raise awareness about obesity as a chronic disease. The results of the current could facilitate targeting prevention activities.Methods: The study included 966 children, 6-15 years of age, from different primary schools in Slovenia. The study was conducted from 2012-2013 using a questionnaire to acquire epidemiologic information about overweight children and was processed using basic statistical methods with SPSS.Results: We showed that 12.7% of children were overweight; 8.4% of children were in the overweightcategory and 4.3% were in the obese category. Of the enrolled children, 77% were of the opinion that their eating habits were suitable, despite the fact that only 66% had 5 meals per day and 61% had breakfast every day. One-half of the children claimed to be physically active and 70% were sedentary < 2 h daily.Conclusion: With respect to excessive nourishment of children, Slovenia ranks lower than other countries. Knowledge about obesity as a chronic disease among Slovenian school children was limited, as was knowledge about different treatments for obesity. Thus, there is a public health need to preventchildhood obesity.
Keywords: obesity; epidemiology; child; healthy lifestyle